2020
DOI: 10.3390/molecules25245899
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Surface Properties of Chitosan-Salts Modified PMMA Denture Base Material

Abstract: Chitosan (CS) and its derivatives show antimicrobial properties. This is of interest in preventing and treating denture stomatitis, which can be caused by fungi. Therefore, the aim of this study was the development of a novel antifungal denture base material by modifying polymethyl methacrylate (PMMA) with CS-salt and characterizing its antifungal and surface properties in vitro. For this purpose, the antifungal effect of chitosan-hydrochloride (CS-HCl) or chitosan-glutamate (CS-G) as solutions in different co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…Alternatively, natural polymers have been attempted as novel methods to enhance the antimicrobial properties of dental appliances. For example, polymethyl methacrylate (PMMA) was modified with chitosan, a natural polymer with antibacterial and antifungal properties [47,48]. Nawasrah et al found that adding henna (Lawsonia inermis), an inexpensive natural extract that has antifungal propertie, to acrylic denture base material may control the proliferation of C. albicans [49].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, natural polymers have been attempted as novel methods to enhance the antimicrobial properties of dental appliances. For example, polymethyl methacrylate (PMMA) was modified with chitosan, a natural polymer with antibacterial and antifungal properties [47,48]. Nawasrah et al found that adding henna (Lawsonia inermis), an inexpensive natural extract that has antifungal propertie, to acrylic denture base material may control the proliferation of C. albicans [49].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Walczak et al (33) reported that, while chitosan salts had antifungal activity, adding chitosan salt powders to denture base materials had no antifungal, antibiofilm, or anti-adherent effects.…”
Section: Discussionmentioning
confidence: 99%
“…Modification of PMMA with chitosan was proposed by Walczak et al in order to achieve an antifungal effect. However, the results obtained are not satisfactory and require further investigation [ 80 ].…”
Section: Oral Applications Of Natural Polymersmentioning
confidence: 99%